1996
DOI: 10.1093/nar/24.11.2022
|View full text |Cite
|
Sign up to set email alerts
|

The NMR structure of 31mer RNA domain of Escherichia coli RNase P RNA using its non-uniformly deuterium labelled counterpart [the 'NMR- window' concept]

Abstract: The NMR structure of a 31mer RNA constituting a functionally important domain of the catalytic RNase P RNA from Escherichia coli is reported. Severe spectral overlaps of the proton resonances in the natural 31mer RNA (1) were successfully tackled by unique spectral simplifications found in the partially-deuterated 31 mer RNA analogue (2) incorporating deuterated cytidines [C5 (>95 atom % 2H), C2' (>97 atom % 2H), C3' (>97 atom % 2H), C4' (>65 atom % 2H) and C5' (>97 atom % 2H)] [for the 'NMR-window' concept se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The combined data suggest that, in particular, residues G292 and G293 in M1 RNA are exposed and accessible for base-paring with the substrate and are not involved in conventional Watson-Crick interactions with other parts of M1 RNA; for example, nucleotides in the upper part of the internal loop. This is also supported by our studies in which the structure of an RNA representing the P7-loop was determined by NMR spectroscopy (Glemarec et al, 1996). Thus, we conclude that the structural integrity of the P7-loop is important in making the conserved GGU motif accessible for base-pairing (see also below).…”
Section: G292 G293 and U294 In M1 Rna Are Accessible For Base-pairinsupporting
confidence: 80%
“…The combined data suggest that, in particular, residues G292 and G293 in M1 RNA are exposed and accessible for base-paring with the substrate and are not involved in conventional Watson-Crick interactions with other parts of M1 RNA; for example, nucleotides in the upper part of the internal loop. This is also supported by our studies in which the structure of an RNA representing the P7-loop was determined by NMR spectroscopy (Glemarec et al, 1996). Thus, we conclude that the structural integrity of the P7-loop is important in making the conserved GGU motif accessible for base-pairing (see also below).…”
Section: G292 G293 and U294 In M1 Rna Are Accessible For Base-pairinsupporting
confidence: 80%
“…Chemical shift mapping data were available in certain cases without corresponding K d values because titration spectra were recorded with reduced resolution in the indirect dimension. (C) Electrostatic surface potential of P4 computed using the B-type X-ray structure (Glemarec et al 1996;Kazantsev et al 2005) with negative and positive potentials indicated in red and blue, respectively.…”
Section: +mentioning
confidence: 99%
“…In the ribozyme reaction, the P15 loop has been shown to base pair with the 3′-CCA sequence of the substrate pre-tRNA (and product) (28,120). Kinetic and biophysical analysis suggested that there might be a metal ionbinding site in the bacterial P15 loop (121)(122)(123). However, this interaction may be less important in the cleavage catalyzed by the bacterial holoenzyme (123).…”
Section: (18)mentioning
confidence: 99%